Development and experimental study of a high-efficiency helium twin-screw compressor. (June 2021) - Wang, Chuang; Xing, Ziwen; Sun, Shizhong; Yu, Zhiqiang
Highlights: The development of a high-efficiency oil-injected helium twin-screw compressor is introduced. Several methods were adopted to overcome some intractable problems about leakage and high temperature rise. An experiment is performed on two developed compressors to demonstrate their high-efficiency. Abstract: Large-scale cryogenic refrigeration equipment is the sole way to realize the cryogenic environment for scientific facilities such as space technology, quantum computer and magnetic levitation. As one of the key moving components in cryogenic system, the helium compressor determines the reliability and performance of the whole cryogenic system. The twin screw compressor is a promising choice to be used in large-scale cryogenic refrigeration system due to its high efficiency and reliability. It can also be used in helium refrigeration cycle to produce liquid hydrogen for hydrogen fuel cells which are paid much attention recently. This paper presents the development of a high-efficiency oil-injected helium twin-screw compressor. In order to realize its high efficiency and reliability, several methods were adopted to overcome some intractable problems about leakage and high temperature rise. The profile was designed specially for this application. Optimized design and control of clearances were planned to compensate the thermal deformation due to the heat of compression. In addition, a special layout of two-stage mechanical seal was established to prevent helium from leaking into outside environment. To keep the purity of helium, the combined oil separator was selected to separate oil from discharge helium. Moreover, a performance test of the compressor has been carried out. The results demonstrate that the developed oil-injected helium twin-screw compressor has excellent performance.